Understanding genetics: a molecular approach - Norman V Rothwell (John Wiley and Sons, 1993)
The book can be used in a one-semester course or as a guide for two semesters depending on the specific goals of the instructor and student preparation. It should prove to be a reference work for anyone with a basic science background who wishes to become familiar with the accomplishments of molecular genetics